Quantitative descriptive analysis, non-targeted metabolomics and molecular docking reveal the dynamic aging and taste formation mechanism in raw Pu-erh tea during the storage - Bingsong Ma; Cunqiang Ma; Binxing Zhou; Xuan Chen; Yuhua Wang; Yifan Li; Junfeng Yin; Xinghui Li (Food Chemistry: X)
Natural storage promotes raw Pu-erh tea (RaPT) aging along with chemical conversion and flavor evolution. In this study, quantitative descriptive analysis (QDA) and UHPLC-Orbitrap-MS/MS-based non-targeted metabolomics were performed to illustrate dynamic changes of taste compounds across 18 RaPT samples during the storage. Multivariate statistical analyses effectively classified stored RaPT into three groups based on storage stages, confirming that storage duration, rather than environmental conditions, primarily influences the taste profile and the changes in non-volatile compounds. A total of 509 characteristic metabolites (VIP > 1.0, P < 0.05, and FC > 1.50 or < 0.67) including multifarious flavor compounds related to tastes evolution were identified. Notable changes included the reduction, transformation, and condensation of flavonoids (such as catechins, flavonol glycosides, and anthocyanins) and amino acids, alongside an accumulation of organic acids, catechin/amino acid derivatives, flavoalkaloids, and gallic acid. These transformations generated significantly (P < 0.05) decreased umami, bitterness, and astringency, while significantly (P < 0.05) increasing sourness and kokumi. Molecular docking analyses further revealed that certain compounds, notably puerins and N-ethyl-2-pyrrolidone-substituted flavan-3-ols (EPSFs), exhibit high binding affinities with CaSR and OTOP1, contributing to the kokumi and sourness taste profiles.